Bilingual patient navigator or healthcare interpreter: What’s the difference and why does it matter? - Ineke H. M. Crezee (Cogent Medicine, 2019)
This study describes the Bilingual Patient Navigator Program at Seattle Children’s Hospital, comparing the Navigator’s role to that of the professional interpreters also provided by the hospital. The study uses individual and group interviews to investigate why the bilingual patient navigators have been more effective than interpreters alone in impacting no-show rates, number of unplanned hospitalizations, average length of stay, and staff/family confidence in the family’s ability to care for the patient at home among families who were previously experiencing difficulty navigating the healthcare system. Critical differences were found to be the navigator’s freedom to build trust with a patient’s family over time, to point out missed inferences, to restate physician speech into plain language, to alert providers to barriers to implementation of treatment plans, and to teach families basic skills such as preparing for a medical appointment and how to talk with doctors. Implications for healthcare systems serving LEP patients are discussed and further research suggested.